De alienígenas chinos e indígenas yaquis (ubicando el constitucionalismo latinoamericano) - Clavero, Bartolomé (Anuario de Historia de América Latina, 2018)
Here is a couple of past cases in search of a current category. The cases are that of the Yaqui people in Mexico, between their harassment and subjugation in Sonora and their deportation to and enslavement in Yucatan, and that of Chinese immigration and its harshly discriminatory treatment in the same state of Sonora – till their expulsion. The category is the one which might be able to characterize Latin American constitutionalism by the recurrence of similar cases with respect to both indigenous peoples and non-European immigrant contingents. For this purpose, the United States is also taken into account. Among cases and category, the essay deals with the constitutional condition or rather extra-constitutional status, during the 19th century, of the so-called coolíes, of other indentured servants, of former enslaved people and, in their turn, of indigenous peoples as the most significant human presence regarding the very core of constitutionalism. In this context, Latin American constitutional history has revealed itself as a kind of recycling and even strengthening, by independent States, of the European colonial legacy. In other words, throughout the Americas, colonialism may be considered a major factor in the formation and development of constitutionalism.